Triggering Receptor Expressed on Myeloid Cells-2 (TREM2) Interacts With Colony-Stimulating Factor 1 Receptor (CSF1R) but Is Not Necessary for CSF1/CSF1R-Mediated Microglial Survival - Cheng, Baoying; Li, Xin; Dai, Kai; Duan, Shengshun; Rong, Zhouyi; Chen, Yingmin; Lü, Liangcheng; Liu, Zhaoji; Huang, Xiaohua; Xu, Huaxi; Zhang, Yun-Wu; Zheng, Honghua (Frontiers in Immunology, 2021)
Triggering receptor expressed on myeloid cells-2 (TREM2) and colony-stimulating factor 1 receptor (CSF1R) are crucial molecules for microgliopathy, which is characterized by microglia dysfunction and has recently been proposed as the neuropathological hallmark of neurological disorders. TREM2 and CSF1R are receptors expressed primarily in microglia in the brain and modulate microglial activation and survival. They are thought to be in close physical proximity. However, whether there is a direct interaction between these receptors remains elusive. Moreover, the physiological role and mechanism of the interaction of TREM2 and CSF1R remain to be determined. Here, we found that TREM2 interacted with CSF1R based on a co-immunoprecipitation assay. Additionally, we found that CSF1R knockdown significantly reduced the survival of primary microglia and increased the Trem2 mRNA level. In contrast, CSF1R expression was increased in Trem2-deficient microglia. Interestingly, administration of CSF1, the ligand of CSF1R, partially restored the survival of Trem2-deficient microglia in vitro and in vivo. Furthermore, CSF1 ameliorated Aβ plaques deposition in Trem2-/- ; 5XFAD mouse brain. These findings provide solid evidence that TREM2 and CSF1R have intrinsic abilities to form complexes and mutually modulate their expression. These findings also indicate the potential role of CSF1 in therapeutic intervention in TREM2 variant-bearing patients with a high risk of Alzheimer's disease (AD).